The Singing Ornamentation of Lagu Melayu Asli - Hassim, Dayang Siti Hazar Awang; Karim, Kamarulzaman Mohamed (Jurnal Seni Musik, 2023)
Ornamentation is a source of beauty and uniqueness for each Lagu Melayu Asli singer. The ornamentation in Lagu Melayu Asli is better known as lenggok, bunga lagu, air lagu (Suflan, 2015; Rosny, 2018), cengkok, grenek, or gerenek (Silitonga, 2011; Zulaikha, 2008; Suflan, 2015; Rosny, 2018), and some researchers are more comfortable naming it melismatic (Ritawati, 2017). Although Lagu Melayu Asli music in the Malay world is rich in the beauty of ornamentation, guidelines on ornamentation are not specifically stated but rather are to be played or sung by heart and by improvising on the basis of knowledge learned verbally from their idols or teachers (Rosny, 2018; Suflan, 2015; Rizaldi, 2010; Zulaikha, 2008). The systematic distillation in this writing uses a qualitative literature study methodology derived from the articles and interviews of Lagu Melayu Asli. In general, a literature review can be thought of as a more or less methodical method of compiling and analyzing earlier studies (Baumeister & Leary, 1997; Tranfield, Denyer, & Smart, 2003). This study provides literature reviews and concludes guidelines for singers by placing specific categories of ornamentation in Lagu Melayu Asli.